7-Amino-3-phenyl-2-methyl-pyrazolopyrimidine derivatives inhibit human rhinovirus replication - Chakrasali, Prashant; Hwang, Dasom; Lee, Joo-Youn; Jung, Eunhye; Lee, Hye Lim; Reneesh, Alba; Skarka, Adam; Musilek, Kamil; Nguyen, Nhung Hong; Shin, Jin Soo; Jung, Young-Sik (European journal of medicinal chemistry, 2024)
Small molecules that exhibit broad-spectrum enteroviral inhibitory activity by targeting viral replication proteins are highly desired in antiviral drug discovery studies. To discover new human rhinovirus (hRV) inhibitors, we performed a high-throughput screening of 100,000 compounds from the Korea Chemical Bank library. This search led to identification of two phosphatidylinositol-4-kinase IIIβ (PI4KIIIβ) inhibitors having the pyrazolo-pyrimidine core structure, which display moderate anti-rhinoviral activity along with mild cytotoxicity. The results of a study aimed at optimizing the activity of the hit compounds showed that the pyrazolo-pyrimidine derivative 6f exhibits the highest activity (EC50 = 0.044, 0.066, and 0.083 μM for hRV-B14, hRV-A16, and hRV-A21, respectively) and moderate toxicity (CC50 = 31.38 μM). Furthermore, 6f has broad-spectrum activities against various hRVs, coxsackieviruses and other enteroviruses, such as EV-A71, EV-D68. An assessment of kinase inhibition potencies demonstrated that 6f possesses a high and selective kinase inhibition activity against PI4KIIIβ (IC50 value of 0.057 μM) and not against PI4KIIIα (>10 μM). Moreover, 6f exhibits modest hepatic stability (46.9 and 55.3 % remaining after 30 min in mouse and human liver microsomes, respectively). Finally, an in vivo study demonstrated that 6f possesses a desirable pharmacokinetic profile reflected in low systemic clearance (0.48 L∙h-1 kg-1) and modest oral bioavailability (52.4 %). Hence, 6f (KR-26549) appears to be an ideal lead for the development of new antiviral drugs.
Keywords: Animals; Antiviral Agents; vztah mezi dávkou a účinkem léčiva; Rhinovirus; pyrimidiny; inhibitory proteinkinas; mikrobiální testy citlivosti; antivirové látky; Molecular Structure; fosfotransferasy s alkoholovou skupinou jako akceptorem; Pyrazoles; Structure-Activity Relationship; lidé; pyrazoly; replikace viru; Mice; myši; molekulární struktura; Microbial Sensitivity Tests; Dose-Response Relationship, Drug; Protein Kinase Inhibitors; vztahy mezi strukturou a aktivitou; Phosphotransferases (Alcohol Group Acceptor); zvířata; Virus Replication; Pyrimidines; Humans